Traffic Light Planning, Simpang Three Signaled (Junction Of Dolokgede Purwosari Road - Purwosari Padangan Bojonegoro District) - Novianto, Herta; Yanto, Yanto; Ismanto, Ikko Bagus (Jurnal Ilmiah Global Education, 2025)
Intersections are locations of traffic conflicts. The absence of traffic lights or traffic lights at the intersection of Jalan Dolokgede - Purwosari and Jalan Raya Purwosari - Padangan means that vehicles often experience traffic jams and are also prone to traffic accidents. There needs to be traffic management implemented, especially traffic lights or traffic lights, to regulate these unsignaled intersections. The research limits the problem by discussing intersection conditions, traffic volume, saturation flow, effective green time, capacity, degree of saturation, queue length and delays. Traffic light calculations were carried out using the PKJI 2023 method. The results of two-phase intersection planning calculations resulted in a western approach DJ of 0.535, an eastern approach of 0.456, a southern approach of 0.507, an average intersection delay of 9 seconds/SMP with an intersection cycle time of 29 seconds. Meanwhile, the results of the three-phase fire intersection planning produced a western approach DJ of 0.65, an eastern approach of 0.654, a southern approach of 0.643, an average intersection delay of 21.2 seconds/SMP with an intersection cycle time of 46 seconds. The regulation of the unsignaled intersection of Jalan Dolokgede - Purwosari and Jalan Raya Purwosari - Dolokgede can be carried out using either two phases or three phases in accordance with the PKJI 2023 guidelines with DJ ≤0.85.